Comparison of Three Different Fertigation Strategies for Drip Irrigated Table Grapes – Part III. Growth, Yield and Quality - Howell, C.L.; Myburgh, P.A.; Conradie, W.J. (South African Journal of Enology and Viticulture, 2016)
A field trial was carried out in a drip irrigated Dan-ben-Hannah/Ramsey vineyard near Paarl in the Berg River Valley region of South Africa to compare three fertigation strategies. Fertilisers were applied (i) two weeks after bud break, fruit set and post-harvest (LF), (ii) weekly from two weeks after bud break until ten weeks after harvest, except during berry ripening (WF), and (iii) in daily irrigation pulses (DF). Grapevines of all treatments received c. 116 kg/ha N, 22 kg/ha P and 92 kg/ha K per season. Grapevines of all the fertigation strategies were thinned to obtain a normal and high crop load, which is 26 and 36 bunches per grapevine respectively for Dan-ben-Hannah. Crop load did not affect vegetative growth, berry size or bunch mass. However, compared to LF and WF, DF increased the berry size of grapevines bearing 26 bunches. Crop load tended to reduce juice TSS, irrespective of fertigation strategy, particularly in 2002/03. Neither fertigation strategy nor crop load affected TTA and pH. Less berry crack contributed to a higher yield and higher export percentage of the DF grapes. In addition, bigger berries, and therefore better appearance, also contributed to the higher export quality of the DF grapes. Although the DF grapevines bearing 36 bunches produced grapes of poorer colour and overall impression, they were within export norms. Based on the foregoing, the DF strategy should not be regarded as the ultimate solution for table grape production. However, it can be recommended for vineyards on poor soils or where berry crack occurs commonly.